Pengaruh Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty Terhadap Keputusan Pembelian Iphone (Studi Kasus Pada Mahasiswa Fakultas Kedokteran Universitas Islam Malang) - M. Muzammil; N. Rachma; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine the effect of Brand awareness, Brand Association, Perceived quality, Brand loyalty on purchasing decisions for Iphone smartphones in medical students of the Islamic University of Malang. This study uses quantitative research, namely by using a questionnaire to 100 respondents. The data analysis technique used in this study is multiple linear regression. It was found that Brand awareness had a positive effect on purchasing decisions. Brand Association has a positive effect on purchasing decisions. Perceived quality has a positive effect on purchasing decisions. Lastly, Brand loyalty has a positive effect on purchasing decisions. Keywords: Brand awareness, Brand Association, Perceived quality, Brand loyalty, Purchasing Decisions